KAJIAN LAYANAN PURNA JUAL - Heny Sukesi (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2009)
Since 1999, government has issued Consumer Protection Act No. 8/1999. Following the act, in 2002, Government has issued Industry and Trade Ministry Decree No. 634/MPP/Kep/9/2002 to monitor good and service distribution. One of focus of the decree is to regulate the implementation of “after sales service” The problems of after sales service are occurred in regulation and implementation terms, such as: lack of comprehensive monitoring program and lack of consumer awareness toward “after sales service”. The findings of this research are: (i) The “after sales service” regulation have not been implemented optimally. A lot of goods and services are distributed without appropriate guarantees, (ii) the implementation of the regulation faces with a lack of resources to conduct monitoring and supervision activities; (iii) Producers perceive that the implementation of sales service program has less benefit on the improvement of market share (73,6 % of respondent) and the increasing their omzet (55.5 % of respondent); and (iv) there are only about 42,9% of consumers prefer to purchase of good and service in market/shop that have good after sales service. Based on the findings, it is recommended for government to: (i) revise the industry and Trade Ministry Decree No.547/MPP/Kep/7/2002 for Guidelines of Manual Registration and guarantee Card for Information Technology and electronic product. The decree should explicity point out in title provision, definition, product criteria, scope, and responsibility of seller; and (ii) improve the awareness of producer abouturgency of “after sales service” and the monitoring activities through supervisor resource, socialization of regulation, monitoring periodically and publishing “after sales service” assessment, such us customer satisfaction index, and finally improve the access of information for consumer and enhance their awareness concerning after sales sevices.